EVALUATION OF INTERNET ACCESS BY STUDENTS AT A FEDERAL EDUCATIONAL INSTITUTION IN NORTHERN BRAZIL - Kristian, Adris; Nascimento-e-Silva, Daniel (International Journal of Professional Business Review, 2024)
Objective: This study presents the results of assessing Internet access by students at a federal educational institution in northern Brazil.